عادات العقل السائدة لدى مُعلمي ومُعلمات مؤسسات التربية الخاصة في ضوء بعض المتغيرات - حسن, ئافان عبدالله (Sulaimani Journal for Humanities, 2021)
The present study aimed to revealing the level of the prevailing habits of mind of the teachers of special education institutions and to find out whether the habits of mind differ according to some variables such as: (type of institution: public- private, gender, years of experience), the sample consisted of (102) teachers in public & private institutions for the academic year (2020-2021), they were chosen by a simple random method, in the study used a scale that prepared by the researcher according to Costa's theory, which comprised (16) habits of mind, then the validity and reliability of the scale were verified, as the method of the study the descriptive method was used. By (SPSS) program the data were statistically processed. the results of the study revealed that the teachers of special education institutions level of habits of mind was very high, and there are statistically significant differences in the habits of mind the teachers of special education institutions due to variables (type Institution, gender, years of service). Based on these results, the researcher has concluded with a number of recommendations and suggestions.
Keywords: Habits of Mind; Special Education Teacher